The Significance of Sunday School as a Form of Non-Formal Education (A Phenomenological Study at St. Ambrose Church, Tabing Parish) - Agnes Noftri Yanti; Alim Harun Pamungkas (Universitas Negeri Padang, 2026)
This study was motivated by the Sunday School activities which are generally understood only as faith formation activities for children in the church, but have not been widely examined as a form of nonformal education practice. This study aims to identify the reasons for the interest of Sunday School companions in serving and to understand the meaning of Sunday School as a practice of nonformal education at St. Ambrosius Church, Stasi Tabing. This research employed a qualitative approach based on a phenomenological research design. The informants of this study were Sunday School companions who were directly involved in children’s faith formation activities. Data were collected through interviews, observations, and documentation. Data analysis used the interactive model of Miles and Huberman which includes data reduction, data display, and conclusion drawing. The results show that the interest of the companions in serving is driven by a sense of calling to serve, concern for children's faith development, and support from the church environment. In addition, Sunday School is interpreted as a means of faith formation and character building for children through a learning process that is flexible, participatory, and contextual as a practice of nonformal education.